Molecular identification of the causal locus for the petaloid phenotype in Daucus carota - Fujii, Sota (Breeding science, 2019)
Homeotic alteration phenotype of the flowers in Daucus carota are widely used for hybrid breeding, consequently molecular markers tightly-linked to such phenotype are in demand. Here we report the identification of a gene locus responsible for the phenotypic expression of stamen conversion into a petal-like structure, or petaloid. Using a segregating population and sequencing analysis of two bulked populations, we discovered a large contributing peak on the long arm of chromosome 4. DcMADS2, a homolog of the B-class floral homeotic gene PISTILLATA, found at the center of the peak region, was considered the strongest candidate causal gene. We established PCR primers that could be used to distinguish the two DcMADS2 alleles linked to each petaloid- and non-petaloid-phenotype